Entre la carne y el espíritu: el sublime burkiano en “La caída de la casa Usher” de Edgar Allan Poe (2017)
The article proposes a reading of the story “The fall of House Usher”, published in 1839 by the writer Edgar Allan Poe, based on an explanatory process that above all, tries to identify the contact points between Poe’s text and the theory of the sublime postulated by the Irish scholar, Edmund Burke in his aesthetic treatise (1757). The reading of the story, in light of the sublime is a critical-methodological example that should extend the interpretative possibilities of the canonical texts as new questions try to understand what form the category of the sublime contributed with genesis and the valuation of the critical appreciation of the literary gothic works. The hypothesis of the written part of the sublime is a compositional resource that Edgar Allan Poe used in the writing of the story “The fall of House Usher”. The adpoted reading perspective could expand to other texts of the North American storyteller, given the perception of the elements which sustain his text (and that drive the reader towards the feeling of the sublime) and make it possible to identify other features of the wide creative quality that are reliably found in the poetry of Poe.